Effects of compatibilizers on mechanical and antibacterial properties of injection molded nano-ZnO filled polypropylene - Altan, Mirigul; Yildirim, Huseyin (SAGE PUBLICATIONS LTD, 2012)
Polypropylene (PP)/zinc oxide (ZnO) nanocomposites were prepared by melt compounding. Prior compounding, surface of the particles were modified with different compatilibizers such as silane and stearic acid. Modification was also done by coating the particles with maleic anhydride grafted styrene-ethylene-butylene-styrene (SEBS-g-MA) block copolymer dissolved in toluene. Specimens of tensile test, impact test, and antibacterial efficiency test were obtained by injection molding. The results showed that stearic acid and silane containing composites gave structures with fine distributed particles while the presence of SEBS-g-MA induced agglomerates. The presence of stearic acid increased tensile strength and impact strength but reduced elastic modulus. Silane was more effective in increasing elastic modulus. Despite the elastomeric nature of SEBS-g-MA, it did not rise impact strength due to its limited amount of usage in coating of the particles. Antibacterial properties of the composites reduced with the increment of ZnO loading because of the weak UV absorption and insufficient photocatalytic activity of the particles. On contrary, at low ZnO content, satisfactorily high antibacterial effect was observed especially in well dispersed structures including stearic acid and silane.
Keywords: Polypropylene; nano-ZnO; antibacterial property; mechanical property; CALCIUM-CARBONATE; ESCHERICHIA-COLI; THIN-FILMS; NANOPARTICLES; COMPOSITES; IMPACT; NANOCOMPOSITES; POLYSILOXANES; BACTERIA; BEHAVIOR; Materials Science